An analysis of quality human resource management (HRM) practices in Bangladesh ready-made garments sector - Rashid, Farhana; Taib, Che Azlan; Yusoff, Rushami Zien; Ahmad, Mohd Akhir (The Asian Institute of Research, 2019)
Bangladesh Ready-Made Garments (RMG) had grown significantly over the last decades in every term but unfortunately quality of locally produced goods is still an issue. According to BGMEA report (2014) RMG consists around 40% manufacturing as well as 50% of the total workforce and 78% of total export earnings generated from this sector. Most of the employees in RMG are women, around 90%, where 4.2 million people are working in this sector. However, the potential growth and prospect in the Bangladesh RMG sector is huge. And for using these opportunities it should focus on the proper implementation of HR policies to emphasis quality performance. In recent knowledge-based economic condition, human resource is the most crucial resource as organizational effectiveness and efficiency is largely depends on the utilization capacity of this resource, especially in the case of Ready-made Garments industry in Bangladesh. Yet, the realities for RMG organizations are that their people remain undervalued, under-trained, and underutilized. Due to improper HR practices, labor unrest rate in RMG is high, and the employee productivity rate is lower than its competitors. As RMG is the rising sector for further investment, now a day a much concern is needed to improve and sustain garments companies growth. Human Resource Management requires much more concern in the Bangladesh RMG sector. In this aspect, literature proved that HR practices didn’t get much attention, which need to be measured and analyzed in the aspect of Bangladesh RMG sectors quality performance improvement as in RMG sector human resources is the main advantage for industrial growth and sustainable competitive advantage in business. So this study is required to lift up this expectation to fulfill this research gap